A new limnic species of Macrostomum (Platyhelminthes: Macrostomida) from Argentina and its muscle arrangement labeled with phalloidin - Adami, Mariana Laura (2012)
A new species of Macrostomum from limnic environments in Argentina is described. Macrostomum platensis n. sp. differs from its congeners by the shape and length of its stylet. Moreover, the arrangement of the muscle system is described using rhodamine-labeled phalloidin. This method provides detailed information on the complex arrangement of muscles of the body wall, pharynx, head and reproductive organs. The resulting description is compared with previously published ones using the same methodological approach. The muscle arrangement may be considered for future taxonomic studies within the genus Macrostomum and might provide phylogenetically useful characters.